Teachers Voices: A Qualitative Study on Burnout in the Portuguese Educational System - Ana Isabel Mota; João Lopes; Célia Oliveira (MDPI AG, 2021)
Teaching has been identified as an environment of extreme physical, mental, and cognitive demand for teachers and is one of the careers where burnout levels are the highest. This qualitative study aims to (i) understand the importance of personal, organizational, and classroom dimensions concerning the Portuguese education system, (ii) and how these dimensions contribute to burnout in Portuguese teachers from different teaching levels. Semi-structured interviews were conducted with twenty-six primary and high school teachers. Results offer insights on the impact that different variables have on teachers' burnout. The content analysis suggests that organization is the most relevant dimension contributing to teachers' burnout. On the other hand, the classroom category appears to be the most challenging context for teachers to manage. The results highlight the need to consider the dynamics and interdependency between personal, organizational, and classroom dimensions in the development and prevalence of burnout.